2018
DOI: 10.7717/peerj.4556
|View full text |Cite
|
Sign up to set email alerts
|

Copper-induced activation of TRPs and VDCCs triggers a calcium signature response regulating gene expression inEctocarpus siliculosus

Abstract: In certain multicellular photoautotrophs, such as plants and green macroalgae, it has been demonstrated that calcium signaling importantly mediates tolerance to copper excess. However, there is no information in brown macroalgae, which are phylogenetically distant from green algae and plants. We have previously shown that chronic copper levels (2.5 μM) activate transient receptor potential (TRP) channels in the model brown macroalga Ectocarpus siliculosus, allowing extracellular calcium entry at 13, 29, 39 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 65 publications
1
6
0
Order By: Relevance
“…Although NAADP has been shown to trigger Ca 2+ release also in higher plants [ 29 ], its involvement in plant physiological events had yet to emerge. By using Ned-19, a newly-developed chemical probe for NAADP [ 27 ], a NAADP-gated Ca 2+ release was shown to occur in response to copper excess in the marine alga Ulva compressa [ 30 ], as well as in the brown alga Ectocarpus siliculosus [ 31 ]. These data suggest that the spectrum of photosynthetic organisms responsive to NAADP might be broader than previously envisaged.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although NAADP has been shown to trigger Ca 2+ release also in higher plants [ 29 ], its involvement in plant physiological events had yet to emerge. By using Ned-19, a newly-developed chemical probe for NAADP [ 27 ], a NAADP-gated Ca 2+ release was shown to occur in response to copper excess in the marine alga Ulva compressa [ 30 ], as well as in the brown alga Ectocarpus siliculosus [ 31 ]. These data suggest that the spectrum of photosynthetic organisms responsive to NAADP might be broader than previously envisaged.…”
Section: Discussionmentioning
confidence: 99%
“…By using the model legume Lotus japonicus [ 25 , 26 ] stably expressing the genetically encoded Ca 2+ indicator aequorin, we demonstrated that HYTLO1 triggers in plant cells a signal transduction pathway leading to the activation of defence genes in a Ca 2+ -dependent manner. Experiments performed by using the chemical probe Ned-19 [ 27 ] showed that the Ca 2+ signalling pathway activated by HYTLO1 is mediated by nicotinic acid adenine dinucleotide phosphate (NAADP), a metabolite of nicotinamide adenine dinucleotide phosphate (NADP) which has been demonstrated to act as a potent Ca 2+ mobilizing messenger in a wide variety of eukaryotes (see [ 28 ] for a review), including plants [ 29 ], as well as green and brown macroalgae [ 30 , 31 ]. The obtained data provide the first evidence for the involvement of this pyridine nucleotide-based Ca 2+ agonist in a physiological event in higher plants and offer new insights into the mechanism of action of fungal hydrophobins.…”
Section: Introductionmentioning
confidence: 99%
“…The genome of E. Siliculosus encodes 18 TRP channels [2], which are functional TRPs that allow extracellular calcium entry [42]. The genome of C. reinhardtii encodes 10 TRP channels and they are functional mosaic TRPs, as in U. compressa, since they are a combination of human TRPA, TRPC, TRPM, and TRPV [43].…”
Section: U Compressa Genome Encodes Channels For Extracellular Calciu...mentioning
confidence: 99%
“…Due to the rapid development of sequencing technology, low-abundance transcripts at the genome-wide transcription level have been detected. lncRNAs, which are noncoding RNAs longer than 200 nucleotides, have extremely complex and important biological functions; they not only regulate gene expression at the epigenetic, transcription, and posttranscriptional levels but also participate in the regulation of many various biological processes, such as genomic imprinting, chromosome remodelling, and transcriptional activation (Garima et al, 2017;Wang et al, 2017). Recent studies have shown that lncRNAs play an important role in the plant response to external factors.…”
Section: Introductionmentioning
confidence: 99%